PERGESERAN FUNGSI ONDEL-ONDEL MENJADI MATA PENCAHARIAN DI TENGAH PANDEMI COVID-19 - Melita, Yerah (Istek Widuri Jakarta, 2021)
Ondel-ondel as an icon of one of the Betawi cultures in the midst of the COVID-19 pandemic has undergone changes and shifts in function. The shift in function that occurs from ondel-ondel as a culture that should be upheld for its sacredness to ondel-ondel which is converted to function as entertainment and a commodity as a livelihood to meet the needs of life. The ondel-ondel function experienced deviations, especially in ondel- ondel performances during performances, thereby reducing the true meaning of the ondel-ondel cultural function, especially Betawi culture. The impact or consequence of a shift from the actual function makes ondel- onde no longer said to be a high culture but changes its position to make ondel-onde a low culture.